Executive Summary, Discussion and Next Steps: National Food Loss and Waste Models - Axmann, H.B.; Guo, X.; Soethoudt, J.M.; Kok, M.G. (Wageningen University & Research, 2024)
The documents explore the Generalized Linear Modelling (Soethoudt et al., 2024) and the AI-Based Monitoring Approach (Guo et al., 2024), two complementary approaches, for addressing data gaps in national-level Food Loss and Waste (FLW) quantification.